A Buddhist application of corporate social responsibility: qualitative evidence from a case study of a small Thai family business. Issue 2 (3rd May 2016) - Chou, Shih Yung; Chang, Tree; Han, Bo
Abstract : The impact of religion on corporate social responsibility (CSR) engagement has received a great amount of research attention. However, little is known about what and how specific core values of Buddhism influence CSR engagement in the family business setting in Thailand. To explore this gap, we employ a single-case study approach focusing on Chug Yont Engineering Co., Ltd, a small-sized family company in the context of Thailand where Buddhism plays a vital role in people's personal and organizational practices. Our qualitative findings suggest the following: first, Kamma, as the core value of Buddhism, has a strong impact on how the owner articulates his business philosophy; second, the owner's business philosophy affected by Kamma in Buddhism has led to several external and internal stakeholder CSR initiatives undertaken by the company; finally, the company's CSR initiatives have directly and indirectly contributed to improved company reputation, lowered employee turnover, and reduced competitive intensity.